Ballistic impact of hollow-point ammunition on porcine bone - Watson, Kayla E.; Henwood, Bailey J.; Hewins, Kate; Roberts, Andrew; Hazael, Rachael (Wiley, 2023)
Identifying failure mechanisms in skeletal tissue allows a deeper understanding of the effects of specific projectile impacts on bone. While ballistic trauma in flat bones is largely researched, knowledge of how long bones react to gunshot impacts is limited in the literature. The impacts of deforming ammunition appear to produce higher levels of fragmentation; however, these have not been studied in depth. This study compares the damage to femora bone by HP 0.357 and 9 mm projectiles constructed with both full and semi-metal jackets. Impact experiments were undertaken on a single-stage light gas gun involving the use of a high-speed video camera and full reconstruction of the bones to ascertain fracture patterns occurring in the femora. Higher degrees of fragmentation are likened to the presence of semi-jacketed HP projectiles than jacketed HP projectiles. The observations of external facing beveled edges are believed to be associated with the increased separation of the jacket and lead core of projectiles. Additionally, experimentation has shown that the amount of kinetic energy lost postimpact is likely related to the presence or the absence of a metal jacket on an HP projectile. The observed data, therefore, suggest that the composition, rather than the configuration, of a projectile affects the type and extent of the damage.
Keywords: Bone trauma; hollow point; jacketed bullet; ballistic trauma; fracture analysis; firearms